Impact of deeper groundwater depth on vegetation and soil in semi-arid region of eastern China - Zhao, Siteng; Zhao, Xueyong; Li, Yulin; Chen, Xueping; Li, Chengyi; Fang, Hong; Li, Wenshuang; Guo, Wei (Frontiers in Plant Science, 2023)
Understanding the impact of deep groundwater depth on vegetation community and soil at sand dunes with different underground water tables is essential for ecological restoration and the conservation of groundwater. Furthermore, this understanding is critical for determining the threshold value of groundwater depth that ensure the survival of vegetation. This paper was conducted in a semi-arid region in eastern China and the effects of deep groundwater depth (6.25 m, 10.61 m and 15.26 m) on vegetation community and soil properties (0-200 cm) across three dune types (mobile, semi-fixed and fixed dunes) were evaluated in a sand ecosystem in the Horqin Sandy Land. For plant community, different species appeared to alter morphological characteristics to accommodate various groundwater depth. For soil properties, groundwater depth directly influenced soil moisture, total carbon, total nitrogen, available nitrogen, available phosphorus concentrations and soil pH. Besides, groundwater depth indirectly affected organic carbon and available potassium concentrations. In addition, herb was mainly distributed in areas with lower groundwater depth, higher plant nitrogen, higher average height, larger coverage, higher soil organic carbon content, higher species abundance and higher soil nitrogen content, yet arbor and shrub species sparsely distribute in places with deeper groundwater depth. As arbor and shrub are key driver species of ecosystem sustainability, the adaptation of these dominant species to increasing groundwater depth may alleviate the negative effects of increasing groundwater depth, however that restrictions on this adaptation were exceeded at the deeper groundwater depth.